2019
DOI: 10.1111/exd.14064
|View full text |Cite
|
Sign up to set email alerts
|

Skin DNA methylation profile in atopic dermatitis patients: A case–control study

Abstract: Atopic dermatitis (AD) is a chronic, recurrent, inflammatory, immune-mediated dermatosis. Approximately 10%-20% of children and 1%-3% of adults suffer from this disease in developed countries. [1][2][3] AD generally develops in individuals with a polygenic inherited predisposition under the influence of external and internal triggers and is accompanied by several immunological complications. [4][5][6] Many loci affecting genetic predisposition to AD have been identified. [7][8][9][10][11][12][13] However, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…neurodermatitis) is one of the most common and chronic human inflammatory skin diseases whose pathogenesis remains insufficiently clear and for which no curative therapy is currently available. [1][2][3] As a key representative of the small group of so-called "atopic" diseases, AD carries a high burden of disease for affected individuals and their families, and is often triggered or aggravated by psychoemotional stress. 4,5 Since AD steadily increases in incidence and absorbs major health care resources, the development of optimized AD therapeutics that combine efficiency with long-term safety and affordability, especially for children with AD, 6 remains a major unmet challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…neurodermatitis) is one of the most common and chronic human inflammatory skin diseases whose pathogenesis remains insufficiently clear and for which no curative therapy is currently available. [1][2][3] As a key representative of the small group of so-called "atopic" diseases, AD carries a high burden of disease for affected individuals and their families, and is often triggered or aggravated by psychoemotional stress. 4,5 Since AD steadily increases in incidence and absorbs major health care resources, the development of optimized AD therapeutics that combine efficiency with long-term safety and affordability, especially for children with AD, 6 remains a major unmet challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis (AD; syn. neurodermatitis) is one of the most common and chronic human inflammatory skin diseases whose pathogenesis remains insufficiently clear and for which no curative therapy is currently available 1‐3 . As a key representative of the small group of so‐called “atopic” diseases, AD carries a high burden of disease for affected individuals and their families, and is often triggered or aggravated by psychoemotional stress 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Genome‐wide DNA methylation profile study found that differential DNA methylation in the genes belongs to a number of AD‐related processes including immune response regulation, lymphocyte activation, cell proliferation, differentiation and apoptosis, suggesting that DNA methylation is an additional predisposing factor for AD 44 …”
Section: Epigenetic Regulation Of Immunitymentioning
confidence: 99%
“…Previous work has revealed that there are both shared and unique epigenetic mechanisms at work in atopic dermatitis and psoriasis. 52 Cristina de Guzman Strong and colleagues provide an overview of our current understanding of epigenetics in atopic dermatitis. 53 The authors point out that the prevalence of atopic dermatitis has tripled in the past 30 years in industrial countries, raising the possibility that environmental effects, acting through epigenetic mechanisms, maybe at work.…”
Section: Infl Ammatory S K In D Is E a S E S And Their Tre Atmentmentioning
confidence: 99%